Mass Customization - Dash, Priyabrat (International Journal of Psychosocial Rehabilitation, 2019)
Mass customization allows customers to customize their goods and takes more time and money. Mass production is still more preferred type of production.The proposed decision support system can be used to determine the characteristics of the mass-production product as well as mass customization ordering stage.Under mass customization environment, a CAD/CAE integrated customization product approach is proposed.To develop methods for mass customization of the product family, a scale-based modular approach is proposed and requires two systems for designing the product family and product design for customisation.The customisation feature can be accomplished by modifying the scale and replacement values, eliminating individual modules depending on the product family model.CODP is dynamic and following the changes of customized products.The paper provides an idea of product mixes for the new system with a thorough analysis of the process, production and customer order characteristics of the goods in the supply chain, and analyses the key problems in implementing the new mass customization and further investigations.